Speed-up, slowdown, and redirection of ice flow on neighbouring ice streams in the Pope, Smith, and Kohler region of West Antarctica - H. L. Selley; A. E. Hogg; B. J. Davison; P. Dutrieux; T. Slater (The Cryosphere)
The ice streams feeding the Dotson and Crosson ice shelves are some of the fastest changing in West Antarctica. We use satellite observations to measure the change in ice speed and flow direction on eight ice streams in the Pope, Smith, and Kohler region of West Antarctica from 2005 to 2022. Seven ice streams have sped up at the grounding line, with the largest increase in ice speed at Smith West Glacier (87 %), whilst Kohler West Glacier has slowed by 10 %. We observe progressive redirection of ice flowlines from Kohler West into the more rapidly thinning and accelerating Kohler East Glacier, resulting in the deceleration of Kohler West Glacier and eastward migration of the ice divide between Dotson and Crosson ice shelves. These observations reveal previously undocumented impacts of spatially varying ice speed and thickness changes on flow direction and ice flux into downstream ice shelves, which may influence ice shelf and ice sheet mass change during the 21st century.